INTERRELATIONS BETWEEN AUTOCHTHNOUS PROTEROZOIC GRANITE FORMATION AND DEFORMATION PROCESSES IN TALNIV FAULT ZONE (UKRAINIAN SHIELD) - Shevchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The multi-stage formation of the Proterozoic structure formation with the changed rheological mechanisms has been showed on the base of Talniv fault zone. The strong Interrelations between deformation processes and autochthnous two-feldspathic granite-formation have been proved. They were displayed by essential mylonite, migmatite, and granite-gneiss monocline formation. The stage formation and dynamo-cinematic conditions of structure formations based upon structural-paragenetic research in Talniv fault zone have been showed.